Análise dos indicadores de sustentabilidade no município de Juruti-PA em função da atividade de mineração - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This study investigated sustainability indicators in the municipality of Juruti, located in the state of Pará, considering the impact of mining activity, in particular the extraction of bauxite by a mining company. The research addressed socioeconomic, environmental, security and infrastructure dimensions, through interviews and data analysis. The community offered varied opinions on the sustainability of mining, reflecting common challenges associated with this industry. Factors such as rising crime, insufficient infrastructure and environmental issues generated concerns among the population, while also recognizing the economic benefits generated by the activity. The results highlighted the importance of transparency and dialogue between the company, local government and the community to address concerns and seek sustainable solutions. This study contributes to the understanding of the complex dynamics involved in mining and sustainable development in Amazonian regions.
Keywords: Desenvolvimento Sustentável; Atividade de Mineração; Amazônia; Índices; CNPQ:: CIÊNCIAS EXATAS